2021
DOI: 10.1101/2021.01.08.425994
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CRY2missense mutations suppress P53 and enhance cell growth

Abstract: Disruption of circadian rhythms increases the risk of several types of cancer. Mammalian cryptochromes (CRY1 and CRY2) are circadian transcriptional repressors that are related to DNA repair enzymes. While CRYs lack DNA repair activity, they modulate the transcriptional response to DNA damage, and CRY2 can promote SCFFBXL3-mediated ubiquitination of c-MYC and other targets. Here, we characterize five mutations in CRY2 observed in human cancers in The Cancer Genome Atlas. We demonstrate that two orthologous mut… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…In addition, previous studies have revealed CLOCK and BMAL1 as key regulators for acute myeloid leukemia (AML) by contributing to proliferation and stemness [ 66 , 67 ]. Moreover, deletions of Cry1 and Cry2 diminished tumor development in p53 null mice possibly due to triple mutant-induced genotoxic stress [ 68 , 69 ]. Taken together, the dual function of clock genes, either as oncogenes or as tumor suppressors, may be attributed to tissue-specific mechanisms and implies the existence of intricate clock-dependent networks, which are involved in the maintenance of homeostasis during different tumor stages.…”
Section: Regulation Of Circadian Rhythms and Their Functions In Cancermentioning
confidence: 99%
“…In addition, previous studies have revealed CLOCK and BMAL1 as key regulators for acute myeloid leukemia (AML) by contributing to proliferation and stemness [ 66 , 67 ]. Moreover, deletions of Cry1 and Cry2 diminished tumor development in p53 null mice possibly due to triple mutant-induced genotoxic stress [ 68 , 69 ]. Taken together, the dual function of clock genes, either as oncogenes or as tumor suppressors, may be attributed to tissue-specific mechanisms and implies the existence of intricate clock-dependent networks, which are involved in the maintenance of homeostasis during different tumor stages.…”
Section: Regulation Of Circadian Rhythms and Their Functions In Cancermentioning
confidence: 99%